2011
DOI: 10.1161/strokeaha.110.604090
|View full text |Cite
|
Sign up to set email alerts
|

Early Prediction of Outcome of Activities of Daily Living After Stroke

Abstract: Background and Purpose-Knowledge about robust and unbiased factors that predict outcome of activities of daily living (ADL) is paramount in stroke management. This review investigates the methodological quality of prognostic studies in the early poststroke phase for final ADL to identify variables that are predictive or not predictive for outcome of ADL after stroke. Methods-PubMed, Ebsco/Cinahl and Embase were systematically searched for prognostic studies in which stroke patients were included Յ2 weeks after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
310
1
19

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 455 publications
(352 citation statements)
references
References 88 publications
9
310
1
19
Order By: Relevance
“…Age binarized at 80 years is a new predictor identified by the CART analysis. The finding that patients aged 80 years or more needed to be less impaired (SAFE score ≥ 8) in order to achieve the same functional outcome as their younger counterparts is in keeping with previous reports that age is an independent predictor of stroke outcome 2, 20. TMS is only required for patients with a SAFE score less than 5.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Age binarized at 80 years is a new predictor identified by the CART analysis. The finding that patients aged 80 years or more needed to be less impaired (SAFE score ≥ 8) in order to achieve the same functional outcome as their younger counterparts is in keeping with previous reports that age is an independent predictor of stroke outcome 2, 20. TMS is only required for patients with a SAFE score less than 5.…”
Section: Discussionsupporting
confidence: 88%
“…Previous studies have used clinical measures alone to predict upper limb outcomes 2, 3, 4. One study found that patients at 48 h poststroke with a Fugl‐Meyer scale score of at least 1 point for paretic finger extension, and a Motricity Index score of at least 9 points for shoulder abduction, had a 98% probability of having “manual dexterity” 6 months poststroke, defined as an ARAT score of at least 10 points 23.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Models were adjusted for age and discharge gait speed. Age has been recognised as a significant predictor of functional recovery 22 , and gait speed is a predictor of free-living activity in people with chronic stroke 23 . Significance was set at p < 0.05 and SPSS 21.0 was used for all statistical calculations.…”
Section: Resultsmentioning
confidence: 99%